2021
DOI: 10.1053/j.seminhematol.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism in infections: Focus on COVID-19

Abstract: Iron is a micronutrient essential for a wide range of metabolic processes in virtually all living organisms. During infections, a battle for iron takes place between the human host and the invading pathogens. The liver peptide hepcidin, which is phylogenetically and structurally linked to defensins (antimicrobial peptides of the innate immunity), plays a pivotal role by subtracting iron to pathogens through its sequestration into host cells, mainly macrophages. While this phenomenon is well studied in certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 90 publications
4
50
0
3
Order By: Relevance
“…As previously commented, oxidative damage gets aggravated when alterations in iron metabolism are also present [ 47 ]. Iron is transported across the membrane of throphoblasts via the divalent metal transporter DMT1 and released from the basolateral membrane to the bloodstream via FPN.…”
Section: Discussionmentioning
confidence: 99%
“…As previously commented, oxidative damage gets aggravated when alterations in iron metabolism are also present [ 47 ]. Iron is transported across the membrane of throphoblasts via the divalent metal transporter DMT1 and released from the basolateral membrane to the bloodstream via FPN.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of iron metabolism (i.e., increased plasma levels of ferritin and decreased levels of iron and TF saturation) and anemia are frequently described in COVID-19 patients [ 24 , 37 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] and are suggested to play a main role in multiorgan failure of severe SARS-CoV-2 infection. In particular, data from observational studies, which have been confirmed in a large meta-analysis, showed that hemoglobin level decreases, particularly in older people, and is negatively associated with comorbidity and severity of the disease [ 65 , 66 , 68 ].…”
Section: Proposed Mechanisms Of Sars-cov-2 Infection and Ferroptosis Inductionmentioning
confidence: 99%
“…Ferroptosis of non-leukocytic cells often results in the release and activation of a different damage-associated molecular pattern (DAMP), triggering the inflammatory responses [32,33]. Because COVID-19 patients suffered from systemic hyper-inflammation, characterized by ROS elevation and cytokine storm, SARS-CoV-2 infection was predicted to involve ferroptosis [34][35][36]. The prediction was also evidenced by the elevated serum iron load in COVID-19 patients, and the decreased GPX4 expression in SARS-CoV-2 infected cells [37][38][39].…”
Section: Introductionmentioning
confidence: 99%